Beyond the Pathway: Insights for Widening Participation from Graduates who Accessed University via Enabling Programs - Stokes, Jennifer (Journal of University Teaching and Learning Practice, 2025)
Educational access and degree completion highlight gaps in student equity (Department of Education, 2024). Australian enabling programs offer insight supporting students from underrepresented backgrounds through to graduation. These pathways demonstrably improve outcomes for students from government-defined equity groups, in areas such as undergraduate transition and retention (Pitman et al., 2016, p. 4), and undergraduate success (Syme et al., 2022).  This research asks how enabling pedagogy shapes learning for students beyond the pathway program. Semi-structured interviews of two-to-three hours’ duration were held with five graduates from underrepresented backgrounds who entered Australian university via a one-year enabling program (or part-time equivalent). Careful design and purposive sampling ensured strong representation of equity groups, alongside diverse career aspirations and life experience. Interview data was analysed using critical pedagogy to understand systemic marginalisation (Freire, 2004) and thematic Analysis (Braun & Clarke, 2022) to generate deep understanding of how programs support students. Building upon a mixed-methods case study, this research utilises the ADEPT framework for enabling pedagogy (Stokes, 2023) as a theoretical lens for analysing graduate vignettes. This paper articulates how enabling pedagogy better supports these students, providing insights applicable for widening university participation at all levels.